Developing Strategy Of Mude Herun Tourim Object In Pruda Village Waiblama Subdistrict Sikka Regency - Hermin Da Herni, Berndeta (CV RIFAINSTITUT, 2022)
Pruda village has a tourism object that always visited to spare time on every Sunday annd holiday. There is some purpose that conduted by viisttors namely: to refressing, to improve religion income, to bussiness and exceteral. One of the tourism object in Pruda village is Mude Herun beach that located in Waiblama subdistrict – Sikka regency. it is about 75 km from city center. Mude Herun beach has some unique tourist attraction namely: cape, floor stone, white sand, green tree in the midle of sea there and others beautiful scenary. The development strategy in this object is unimprove yet, beacause lowing of Human sources, unawareness of community about tourism, uncomplete the facilitiees and accesibilites. The techniques of data collection used in this research were observate, interview and study document. The data were analyzed by using technique analysis data. The result finding show that condition of Mude Herun tourism object is suitable as a tourism place that has nature scenary in two place are: Puot and Watu Irun Bura beach, The unconcern of local people, local goverment and other institute to develop the stratagy. Beecause of that, the effort to develop the tourist object is directed according to criteria are the priority of the strategy. There were four aspect to develop, namely: Tourist attraction sector, accesibilities sector, facilities, institute, and promote sector.